Instagram filter-based learning: Developing supplementary media for grammar mastery - Pangestu, Erycha Try Apny (Patria Educational Journal (PEJ), 2024)
This research aims to developed supplementary learning media. The preliminary stage of the research based on need analysis were Questionnaire and unstructured interview. The learning media only limited in paper materials and questions. Based on student need analysis questionnaire in the 10 TPM Grade SMK Islam 1 Blitar, 90% students found identify tenses grammar is difficult. The students assumed that grammar must be memorized pattern to make it easier to do English questions. This research based on Borg and Gall development model by using questionnaire as research instrument. Likert-Scale was used as the measurement to analyze the data. Data collection technique used in the research are survey technique and unstructured interview. The step of research includes 1. Need Analysis, 2. Product Development, 3. Application preparation, 4. Testing of the product, 5. Product revision. The subject of this research is 10 student of 10th grade TPM (Mechanical Engineering) SMK Islam in Blitar.